Synthesis and Properties of Novel Silicone-Acrylate Self-Emulsifying Emulsion - Qu1, Yuanyuan; Huang2, Haofei (Asian Journal of Chemistry, 2013)
In this pater, a novel silicone-acrylate self-emulsifying emulsion was synthesized by emulsifier-free emulsion polymerization. Its structure was characterized by FT-IR, DSC and TEM. Owing to emulsifier-free polymerization applied and nano-sized emulsion particle, the performance of the film was excellent and met the commercial standards of film-forming polymer for antifouling coating. This emulsion may provide a new idea and method for the development of environmentally friendly marine antifouling coatings.